Parenchyma–stromal interactions induce fibrosis by secreting CCN2 and promote osteoclastogenesis by stimulating RANKL and CD68 through activated TGF‐β/BMP4 in ameloblastoma. (21st June 2016) - Takebe, Yuichiro; Tsujigiwa, Hidetsugu; Katase, Naoki; Siar, Chong Huat; Takabatake, Kiyofumi; Fujii, Masae; Tamamura, Ryo; Nakano, Keisuke; Nagatsuka, Hitoshi
Abstract : Background: Tumor parenchyma–stromal interactions affect the properties of tumors and their dynamics. Our group previously showed that secreted frizzled related protein (sFRP)‐2 impairs bone formation and promotes bone invasion in ameloblastoma. However, the effects of the secreted growth factors CCN2, TGF‐β, and BMP4 on stromal tissues in ameloblastoma remain unclear. Materials and results: Thirty‐five paraffin‐embedded ameloblastoma cases, ameloblastoma‐derived cell lines (AM‐1), and primary cultures of ameloblastoma stromal fibroblasts (ASF) were used. Immunohistochemistry, MTT assay, Western blotting, and RT‐PCR were performed on these samples. Parenchyma–stromal CCN2 overexpression correlated significantly with fibrous‐type stroma, but not with myxoid‐type stroma, suggesting a role of CCN2 in fibrosis ( P < 0.05). Recombinant CCN2 induction of enhanced ASF proliferation in AM‐1 medium supports this view. Conversely, BMP4 and TGF‐β were expressed in myxoid‐type fibroblasts, but little expression was found in parenchyma. RANKL‐positive and CD68‐positive stromal cell populations were significantly greater in myxoid‐type tumor areas than in fibrous‐type tumor areas, while a higher Ki‐67 labeling index was recorded in ameloblastoma with fibrous‐type stroma. These data suggest that stromal properties influence bone resorption‐related activities and growth rates, respectively. Conclusions: These results suggest that the effects of secreted growth factors are governed by ameloblastoma parenchyma–stromal interactions. CCN2 promotes fibrogenesis independent of TGF‐β signaling. Absence of CCN2 expression is associated with a phenotypic switch to a myxoid‐type microenvironment that is conducive for TGF‐β/BMP4 signaling to promote osteoclastogenesis.